Formulation of Nanostructured Lipid Carrier from a Mixture of Red Palm Oil and Palm Stearin - Abdi Redha; Saniah; Iwan Rusiardy; Muflihah Ramadhia; Mawardi; D. U. M. Susilo; Fenny Imelda (International Journal of Integrative Sciences, 2023)
Red palm oil can be a source of beneficial ingredients in various foods due to its high total carotene level. This work examined the influence of red palm oil to palm stearin ratio on the Nanostructured Lipid Carrier's turbidity, transmittance, viscosity, β-carotene content, color lightness, and hue. For this purpose, Nanostructured Lipid Carriers were prepared by hot homogenizing red palm oil and palm stearin at several ratios (1:9, 2:8, 3:7, 4:6, and 5:5 (w/w)). According to the present investigation, the ratio of red palm oil to palm stearin primarily affected the turbidity, transmittance, viscosity, β-carotene concentration, color brightness, and hue of NLCs. Furthermore, the study found that adding red palm oil significantly raised the NLC's β-carotene content and turbidity. The ratio of red palm oil to palm stearin that produced the most stable NLC was 5:5 (w/w)